The Role of a Solid Personality in Alleviating Occupational Bullying an Analytical Study of the Perspectives of a Purposive Sample of Teachers at the University of Karbala, College of Administration and Economics - Al-Hasnawi, Saleh Mahdi Mohammed (Research Parks Publishers, 2024)
This research aimed to investigate the relationship between the independent variable, Solid Personality, with its dimensions (control, challenge, commitment), and the dependent variable, job bullying, with its dimensions (belittling, undermining work, verbal abuse). The core research question was: